Improved ambient noise correlation functions using Welch's method (2011)
Here, we evaluate the improvement in noise correlation functions (NCFs) gained by dividing ambient seismic records into shorter, overlapping time windows before correlation and stacking (Welch's method). We compare waveform convergence of short duration NCF stacks (e.g. 2, 5, 15 and 50 d stacks) towards the long?term (365 d) NCF stack. We observe short duration NCF improvement when applying Welch's method for non–pre?processed and running normalized time?series and short duration NCF degradation when applied to a ‘one?bit’ normalized time?series. Surprisingly, non–pre?processed time?series provides the quickest convergence to a robust (year?long) NCF. Because of the simplicity of Welch's method, the improved NCF convergence and a minimal increase in computation, we recommend applying Welch's method for future ambient seismic field analyses. Using this approach will likely improve future NCF analyses, particularly for studies with limited duration recordings, high levels of intermittent local or site noise and studies attempting to evaluate temporal variations in subsurface structure.